2021
DOI: 10.1002/jrs.6229
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of rusty oil spotted glaze produced in Linfen kilns (Shanxi province, AD 1115–1368)

Abstract: The Linfen kiln complex, one of the most representative of Shanxi kilns, is famous for its oil spotted glazed ware production. In this work, micro‐Raman spectroscopy was applied to analyze the nature of the rusty oil spot pattern of a bowl fragment from Linfen kilns. Crystals of polygonal shape found in the spots at the glaze surface and around bubbles in the cross‐section of the glaze were identified as hematite. Their distribution in the glaze suggests that nucleation seeds and small crystals are carried tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The majority of the detected Raman peak positions at the spectrum A, B, and C matched well with each other, while few of them shifted slightly due to the faceted aspect of crystal lattice originated from the laser source (λ = 532 nm) and/or phonon confinement effect in our samples [36]. We noticed that spectra of the ε-Fe 2 O 3 phase collected from ancient Fe-rich porcelains were almost the same [10,18,21]. The similarities among Raman spectra taken at "A", "B", and "C" strongly suggested that those three types of crystals clusters shared the same mineral composition.…”
Section: Phase Analysis By Xrd and Rssupporting
confidence: 70%
See 1 more Smart Citation
“…The majority of the detected Raman peak positions at the spectrum A, B, and C matched well with each other, while few of them shifted slightly due to the faceted aspect of crystal lattice originated from the laser source (λ = 532 nm) and/or phonon confinement effect in our samples [36]. We noticed that spectra of the ε-Fe 2 O 3 phase collected from ancient Fe-rich porcelains were almost the same [10,18,21]. The similarities among Raman spectra taken at "A", "B", and "C" strongly suggested that those three types of crystals clusters shared the same mineral composition.…”
Section: Phase Analysis By Xrd and Rssupporting
confidence: 70%
“…ε-Fe 2 O 3 has become a research hotspot as the chromogenic crystals. Researchers also reported the existence of ε-Fe 2 O 3 polymorph in the oil spot Jian wares [19], sauce glaze porcelain from the Qilizhen kiln [20], rusty-oil-spotted glaze at the Linfen kiln [21] and/or Xiao kiln [22], hare's fur glaze of Jizhou kiln [23], brown glaze porcelain of Yaozhou kiln [24], sauce glaze and black glaze porcelains from Qingliangsi site [25], and purple-gold glaze porcelain from the Forbidden City [26]. It is believed that research studies on the growth mechanism of ε-Fe 2 O 3 in ancient porcelains will provide guidance for the artificial synthesis of this promising material, in addition to having a profound impact on Asian ceramic history.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study of the brown glazed stoneware from Yaozhou kiln, iron oxide crystals with a size of 2–3 μm were found on the glaze surface, as well as large dendritic‐like flakes, which are larger than 25 μm (Wen et al, 2019). Most of the ε‐Fe 2 O 3 crystals found in ancient Chinese stonewares, such as Oil Spot and Hare's Fur Jian ware (Dejoie et al, 2014; Liu et al, 2018), purple‐gold glazed stoneware from the Forbidden City (Wang et al, 2019), sauce glazed and black glazed stonewares from Qingliangsi Site Qilizhen kiln, and Linfen kiln (Wang et al, 2021), are organized in a leaf‐like or dendritic‐like manner. It was also found in the bluish white porcelain from Jingdezhen recently (Hoo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Iron‐rich glaze generally embraced relatively higher iron concentration, and the patterns occurred owing to phase separation between the melted glaze and crystallised iron oxide, which had an important position in ancient Chinese porcelain. Upon firing (1240°C), iron minerals in the melting glaze thermally decompose into iron oxide and oxygen, and iron oxide progressively accumulate around the growing oxygen bubbles, then iron‐enriched areas will form on the glaze surface after larger bubbles ultimately release 35–37 . Phase separation takes place with temperature increases, and the surface iron‐rich (flux) spots begin to flow down along the sides of tea bowls.…”
Section: Discussionmentioning
confidence: 99%